RANCANG BANGUN APLIKASI UJIAN AKHIR SEMESTER ONLINE UNTUK MENGUKUR PENCAPAIAN KOMPETENSI SISWA - Respati Bary Mahputra; Andy siswanto (SPIRIT, 2014)
the exam end smester is an activity undertaken by the school to determine the level of students' progress and is the process of student learning outcomes assessment that is implemented at the end. To monitor the development of the quality of education is needed SK. Competence is a combination of knowledge, skills, values and attitudes reflected in the habit of thinking and acting. In this case competence is defined as the knowledge, skills and abilities controlled by a person who has become part of him. This is an application made in the application of information technology to manage the data evaluation includes schools, student data, teacher data, the subjects and the value of the evaluation has been done.. Keywords: exam aplication, education